„Nyugdíjbiztonság jövője” – a nyugdíjrendszer mikroszimulációs modellezésének lehetőségei = ”The future of pension security”: the possibilities of microsimulation modeling of the pension system - Szabó, Mihály Zsolt (Közép-Európai Közlemények, 2018)
One of the most significant societal changes that threaten the Member States of the European Union is the high aging of the population and its present and expected impact on economies and the pension security of citizens. Hungary, like the Member States of the European Union, is aging and is facing different challenges, the most important of which is the health system, the social security and pension system, and the transformation of the tax system. These economic and societal challenges require long-term government strategies, which strategies need to be modeled, tested and verified in some way. In the developed countries of the European Union, a methodology for microsimulation has been applied for a long time, which is becoming more and more popular in Hungary in the impact assessment of measures. The study is structured in three parts. The first section presents the current and future trends of the European Union’s population through statistical analyzes. The second part presents the results of the pension modeling of the Member States of the European Union, including the applicability of the results of operational research in the modeling of pension systems. The third section outlines the partial results of the research project entitled “Economic Impact of Global Aging on Retirement Security”.